Implementasi Fungsi Manajemen Terhadap Efektivitas Kinerja Proyek Refurbishment KRI Fatahillah (361) pada PT Len Industri (Persero) - Nazwa Syaqila; Herry Sutanto (Journal of Science, Technology, and Innovation, 2026)
Defense refurbishment projects require effective management practices to achieve project objectives within predetermined time, cost, and quality constraints. This study analyzes the implementation of planning, organizing, actuating, and controlling (POAC) functions and their contribution to project performance effectiveness in the refurbishment project of KRI Fatahillah (361) at PT Len Industri (Persero) using a qualitative descriptive approach based on in-depth interviews with the Project Controller and descriptive-interpretative analysis. The findings reveal that POAC implementation contributes to project effectiveness through schedule control, resource coordination, operational execution, and performance monitoring, while major challenges arise from procurement specification mismatches, contract-to-execution delays, changing technical requirements, consortium coordination complexity, and limited specialist personnel. Adaptive responses, including replanning, intensive monitoring, risk documentation, strengthened consortium coordination, and managerial escalation, enabled the project to maintain performance objectives despite operational uncertainties. The study proposes an adaptive POAC model that emphasizes responsiveness to technical changes, procurement risks, and stakeholder dynamics as a critical determinant of effectiveness in defense refurbishment projects.